Alternativas para el mejoramiento de producción agrícola en los cultivos de cítricos - Bobadilla Vega, Pedro José (2024)
The present research was based on the compilation of information on alternatives for the improvement of agricultural production in citrus crops. Different sources of information indicate that citrus fruits are crops of economic importance for Ecuador because they constitute the daily diet of the population not only nationally but also worldwide. Different sources of information indicate that citrus fruits are crops of economic importance for Ecuador because they constitute the daily diet of the population not only nationally but also worldwide. The use of this new technology for the agronomic management of citrus crops is a tool to be taken into account, in our production system, as a good alternative to improve the profitability of crops. It is necessary to implement a new methodology to estimate the yield of citrus with high accuracy or at least with a lower error than that of visual methods, it can contribute to increasing the economic profitability of farmers and reducing production costs. In this research, we deal with the different alternatives that exist to improve the agronomic productivity of citrus fruits.